2020
DOI: 10.3390/jcm9051522
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety of Bevacizumab, Ranibizumab, and Aflibercept for Treatment of Neovascular Age-Related Macular Degeneration (AMD): A Systematic Review and Network Meta-Analysis of Direct Comparative Studies

Abstract: Background: Since the efficacy of ranibizumab (RBZ), bevacizumab (BVZ) and aflibercept (AFB) is comparable in neovascular age-related macular degeneration (AMD), we conducted a systematic review and meta-analysis to evaluate the long-term safety profiles of these agents, including ocular safety. Methods: Systematic review identifying randomized controlled trials (RCTs) comparing RBZ, BVZ and AFB directly published before March 2019. Serious ocular adverse events (SOAE) of special interest were endophthalmitis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 29 publications
0
41
0
2
Order By: Relevance
“…Pluykhova et al compared the safety profile of long-term use of ranibizumab, bevacizumab, and aflibercepts in the RCT (randomized clinical trial) meta-analysis, with the study hypothesizing the potential benefits of ranibizumab vs. bevacizumab in terms of a systemic safety profile. However, more direct RCT on ocular safety needs to be conducted to validate these findings further [ 242 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Pluykhova et al compared the safety profile of long-term use of ranibizumab, bevacizumab, and aflibercepts in the RCT (randomized clinical trial) meta-analysis, with the study hypothesizing the potential benefits of ranibizumab vs. bevacizumab in terms of a systemic safety profile. However, more direct RCT on ocular safety needs to be conducted to validate these findings further [ 242 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Over the last few decades, anti-VEGF therapy has revolutionized the treatment of several retinal diseases. To date, anti-VEGF intravitreal injection is the most commonly performed ophthalmic procedure for the treatment of different retinal diseases such as neovascular AMD, diabetic retinopathy, retinal vein occlusion and secondary neovascularization in tumoral or inflammatory diseases [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In neovascular AMD, it has been shown that functional prognosis worsens if treatment by anti-VEGF intravitreal injections is delayed and strongly correlates with visual acuity at the time of the first injection [9]. Various molecules are available (ranibizumab, aflibercept and bevacizumab) and all have been proven to be safe and efficient for controlling MNV [4].…”
Section: Introductionmentioning
confidence: 99%
“…Aflibercept is a human recombinant fusion protein that acts as a soluble decoy receptor for VEGF family members, including VEGF-A, VEGF-B and placental growth factor (PlGF) [ 9 , 10 ]. Aflibercept is approved with the following indications: neovascular age-related macular degeneration, macular edema following retinal vein occlusion, diabetic macular edema and diabetic retinopathy [ 11 , 12 ]. Furthermore, aflibercept exerts in vitro and in vivo anti-inflammatory action, modulating the phosphorylation of extracellular signal-regulated kinases (ERK) and decreasing retinal tumor necrosis factor alpha (TNF-α) release [ 13 ].…”
Section: Introductionmentioning
confidence: 99%